Guerra y redistribución de cargas defensivas. La Unión de Armas en los Países Bajos católicos - Esteban Estríngana, Alicia (Cuadernos de Historia Moderna, 2002)
The purpose of this paper is to analyze the basis of one of the master projects at the reformism of the 1620s, the Unión de Armas, as it was formulated to the catholic Netherlands. The bargaining strategy employed by the sovereign’s representatives is reconstructed carefully in order to underline the partial success of the Brussels government in 1627: the loyal provinces’s acceptance to take part in the «armed confederation » contrasts with non-agreement directed to increase their contributions of an extraordinary kind and to finance a bigger rate of domestic military spending. This was the agreement that Philip IV and the count-duke of Olivares tried to obtain since the beginning, in spite of the differences with the Court of Isabel Clara Eugenia.
Keywords: Seventeenth Century; 1620s; Catholic Monarchy; catholic Netherlands; army of Flanders; military finances; costs of warfare; military spending redistribution